Average Packing Charges for Florida Fresh Citrus, 2002-2003 - Ronald P. Muraro (EDIS)
A survey was sent to Florida fresh citrus packers to collect data on the average “packing charges” for the 2003 season. A total of nine packinghouses from both the Indian River and Interior production regions provided data for the survey. This is not a statistically chosen sample; therefore, the costs may not be representative of Florida's total citrus packinghouse industry. The participants were chosen because of their willingness to participate in the survey. The information reported were “packing charges,” not actual packing costs. This is EDIS document FE431, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published October 2004.